Study of Some Watershed Characteristics Associated with Gully Erosion Development Using Google Elevation Services in Girei Basin Adamawa State, Nigeria (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
A field study was conducted in 2020 to characterize watershed features and digital terrain attributes of the Girei area. Digital mapping tools were applied to assess altitude, basin size and number, slope gradients, drainage channels, and topographic elements. Results showed that altitude ranged from 152 m in lowland areas to 488 m at hilltops. Four basins (watersheds) were identified, with areas of 2,288.1 km², 190.6 km², 41.1 km², and 13.7 km². Vegetation was dominated by grasses and shrubs typical of the savannah, with scattered sheabutter, acacia, eucalyptus, and locust bean trees. Land use was largely rice and sorghum cultivation, often practiced interchangeably. Drainage patterns reflected the relief, with streams and rivers originating from highlands and channel lengths totaling 355.8 km, comprising trunk routes A and B as well as service routes connecting communities. The slopes were classified as level (25%). The long slope distance from the highest elevations to gully areas facilitated runoff, accelerating gully headcut formation and expansion. These findings highlight the susceptibility of Girei to gully development driven by slope gradient, slope length, runoff velocity, and water volume. Management interventions such as runoff barriers and slope stabilization are recommended to mitigate erosion risks.